AN INVESTIGATION INTO THE EXTENT AND CHALLENGES OF ASSESSING STUDENTS’ SPEAKING SKILLS IN SELECTED SECONDARY SCHOOLS: THE CASES OF WOLAYITA ZONE, ETHIOPIA - Bachore, Mebratu Mulatu; Satenaw, Amare (International Journal of Education, 2018)
The main objective of this study was to investigate the assessment of students’ speaking skill in some selected preparatory schools. It was a descriptive survey. The data was collected from teachers and students using questionnaire, interview and classroom observations.  Taro Yemane (1996) formula was used to determine the sample size. Accordingly, 254 students were selected as samples using simple random sampling technique. But, six English language teachers who teach grade 11 students were selected using availably technique. The data collected via questionnaire was filled into SPSS and then, different statistical analysis such as frequency and percentage were computed from the data inserted in to SPSS. The result of statistical analysis was presented in the tables and pie chart. Besides, data obtained from interview were transcribed and categorized according to related themes. The study revealed that English teachers assess speaking skills of their students at different times. But, it was noted that the most teachers assess speaking skill during speaking lessons only. Regarding the frequency, many EFL teachers assess their students always, however, it was disclosed that there are teachers who assess their students speaking once in a month and even in a semester. The findings of the study also disclosed that different factors such as lack of adequate time, lack of sufficient material, large number of students per class, and teacher’s inappropriate way of assessing speaking skill affect the assessment of speaking skill.